Intelligent Data Structuring for Facility Management as Basis for Smart Applications - Wildenauer, Adrian August; Basl, Josef, 1961-; Rohner, Thomas; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2022)
The research gap consists of unspecified data and requirements at the beginning of a construc-tion project that a client has for the facility management (FM) phase of an asset to operate it efficiently and effectively. This with the aim to enable further applications based on Building Information Modelling (BIM). Building owners are dependent on accurate data for the FM. Yet, the data currently available due to digital methods are mostly not structured or do not focus on the FM but on the shorter construction phase. It is therefore only possible to provide additional services and applications to the user, FM and the public with an increased expenditure of resources. The Design Science Research approach is applied. The result is a generic, model-based, reusa-ble and extensible conceptual framework to incorporate FM data based within the three-dimensional model-based design and construction of an asset to enable smart applications, which are introduced. The approach is exemplified by a use case of the reservation of a meeting room. The conceptual framework is composed of empirical data from expert interviews, questionnaires and factual analysis from 13 projects of different sizes. The findings were assessed by an international panel of experts. The conceptual framework shows which phases need which data, who needs them, and which added value can be generated if intelligent data structuring is used at the beginning of the construction project and bridges the gap between requirement and practice.
Vedoucí práce: Josef Basl
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: aplikovaná informatika [obor disert. práce]; disertace; dissertations